Mortality among workers employed in the mining industry in the United States: A 29‐year analysis of the National Health Interview Survey—Linked Mortality File, 1986‐2014. Issue 10 (20th July 2020) - Arif, Ahmed A.; Adeyemi, Oluwaseun
Abstract: Background: Working in the mining industry increases the risk of chronic diseases and mortality. We investigated overall and cause‐specific mortality rates among workers employed in the mining sector in the United States. Methods: We pooled 29 years of National Health Interview Survey (NHIS) public‐use data from 1986 to 2014, with mortality follow‐up until 31 December 2015. We grouped respondents into the mining and nonmining sectors based on the responses given at the time of the NHIS interview. We compared the overall and cause‐specific mortality rates using standardized mortality ratios (SMR) and 95% confidence interval (CI) adjusted for the competing cause of death. Results: From 1986 to 2014, an estimated 14 million deaths were recorded among subjects eligible for mortality follow‐up. Of these, an estimated 50, 000 deaths occurred among those working in the mining sector. A significantly higher overall mortality (SMR = 1.26, 95% CI: 1.17‐1.36), and mortality from heart diseases (adjusted SMR = 1.56, 95% CI: 1.31‐1.83), cancer (adjusted SMR = 1.30, 95% CI: 1.14‐1.48) and unintentional injuries (adjusted SMR = 1.41, 95%CI: 1.03‐1.85) were observed among those employed in the mining sector. When the analyses were restricted to men, only the SMRs for heart disease and cancer remained statistically significant. No elevated SMR for deaths from chronic lower respiratory disease was observed in the study. Conclusion: Workers employed in the mining sector have a significantly increased total death rate and death rates from heart disease, cancer, and unintentional injuries.